Photocatalyzed Radical Cascade Reaction for the Synthesis of CF2CF2-Containing Benz[e]indene Derivatives - Yasui, Motohiro; Ukai, Mayuka; Morita, Masato; Yamada, Shigeyuki; Konno, Tsutomu (Synthesis, 2025)
A photocatalyzed-radical cascade reaction for the synthesis of tetrafluoroethylene (–CF₂CF₂–)-containing benz[e]indene derivatives has been developed. Investigation of the substrate scope reveals that electron-rich arenes accelerate the cascade process. DFT calculations provide insight into the reaction pathway and the role of the additive. Furthermore, application studies demonstrate access to potentially valuable compounds.
Keywords: Fluoroalkylene; Tetrafluoroethylene; Photoredox; Cascade reaction; Benz[e]indene; Radical reaction; Hydrazones; Cyclization